Case Report: Analysis of four cases of metastatic bladder masses after radical prostatectomy - Wang, Hao; Xie, Dawei; Lu, Jun; Chu, Yifan; Wang, Siqi; Qiao, Peng; Wu, Liyang; Wang, Jianwen (Frontiers in Oncology, 2023)
Objective: To investigate the clinical characteristics, diagnostic and therapeutic methods of bladder metastasis after radical prostatectomy and to improve its diagnosis and treatment. Methods: The clinical data of four patients with bladder metastasis after radical prostatectomy were retrospectively analyzed from January 2011 to December 2021. Three cases suffered from intermittent gross hematuria, only one case was found elevated PSA value. Four cases were performed transurethral resection of bladder tumor, including 1 case who also underwent transurethral resection of prostate tumor. Three cases received endocrine therapy, one of which added intravesical instillation and radiation therapy. Another case received chemotherapy based on comprehensive treatment. Results: According to the pathological and immunohistochemical results, 3 were acinar adenocarcinoma of the prostate with Gleason score of 9, and all were PSA positive and negative for CK7 and GATA-3. One case was small cell neuroendocrine carcinoma of the prostate and was positive for CGA, SYN and CD56. During the follow-up period of 4 to 13 months, 1 case was lost to follow-up and 3 cases were alive. Conclusions: Bladder metastasis after radical prostatectomy is rare, and pathology combined with immunohistochemistry is the gold standard for its diagnosis. Pathological type determines its treatment. Systemic treatment is essential, local treatment is mostly palliative means. Early diagnosis and treatment is significant for better prognosis.